AKIBAT HUKUM WAN PRESTASI DARI SALAH SATU PIHAK DALAM NON DISCLOSURE AGREEMENT (PERJANJIAN KERAHASIAAN) YANG SULIT DIBUKTIKAN KEBENARANNYA - Michael Jeffrey (Universitas Islam Sumatera Utara, 2021)
Non Disclosure Agreement is generally an agreement to disclose confidential information which can be in the form of Intellectual Property Rights or trade secrets. The formulation of the problem in this research is how the rights and the obligations as well as the legal protection of trade secrets in a Non Disclosure Agreement? What is the form of default in the case of PT. Basuki Pratama Engineering with PT. Hitachi Construction Machinery Indonesia? What is the analysis of the judge's considerations and the decisions in the cassation decision number: 3305 K/Pdt/2016 which is difficult to be prove the truth? The results of this research are First, the rights and the obligations in the Non Disclosure Agreement can be added to the clauses that have been agreed by the parties. This is done to protect confidential information held by the owner of the trade secret. Second, the default that generally occurs in the Non Disclosure Agreement is the misuse of confidential information that is used without the consent of the owner of the confidential information, and the resolution of this problem can be carried out by means of a civil lawsuit in the court. For these violations, there are legal consequences such as lawsuits by the owner of confidential information to the recipient of confidential information and the recipient of confidential information can be charged with his action under the Article 17 paragraphs (1) and (2) of the Trade Secret Law Number 30 of 2000. Third, in the legal case studied in this thesis, the judge has punished the defendants by holding the defendants accountable for material and immaterial losses by taking into account the evidence and the statements of the parties in order to give a fair decision for the parties.Keywords: Confidentiality Agreement, Information, Trade Secret.